A NEW CLASS OF OPEN AND CLOSED MAPPINGS - Jha, Purushottam (International journal of advanced research in computer science, 2018)
The purpose of this paper is to introduced and study new classes of open and closed functions called and maps by using and [10] sets and establish relationships of these maps with already existing generalized maps. Several properties of these new notions have been discussed and the connections between them are studied. 2010 Mathematics Subject: Classification. Primary: 54A05, 54C05, 54C08; Secondary: 54C10, 54D10.